Factors Affecting Socialization from the Perspective of the Study of a School Child - Napora, Elżbieta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim was to observe factors which favour or hinder socialization of a child age 11-13. 192 pupils from 10 Polish schools were researched, with the use of a classical sociometric J. Moreno test. The results revealed that the analyzed factors: sex and age of a child as well as structure and material status of a family, number of siblings and place of living do not have a clear influence on the socialization of a school-aged child.